Pengaruh Live Streaming TikTok dan Electronic Word of Mouth Terhadap Keputusan Pembelian Di Caldera Corner - Niken Rahayu Lestari; Dicki Kusmayadi (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to determine the effect of TikTok live streaming and electronic word of mouth on consumer purchasing decisions at Caldera Corner. The research method uses a quantitative descriptive approach. Data was collected through questionnaires distributed via TikTok social media to consumers who have watched Caldera Corner's TikTok live sessions. The sample was obtained using the Cochran formula with a total of 100 respondents. The results showed that simultaneously, the two independent variables had a significant effect on purchasing decisions, with an F test significance value of 0.000 and an R² value of 0.407, which means that 40.7% of the variation in purchasing decisions can be explained by TikTok live streaming and electronic word of mouth. Partially, TikTok live streaming has a significance of 0.003 with a coefficient of 0.260, while electronic word of mouth is 0.000 with a coefficient of 0.330. It can be concluded that both variables play an important role in driving consumer purchasing decisions.